211k views
2 votes
If f(x) = 2x - 9, which of the following are correct? Select all that apply.

f(-3) = 15
f(-1) = -11
f(0) = -9
f(2) = 5
f(3) = -3

User Shadoe
by
6.6k points

2 Answers

5 votes
answer

f(-3) = 15
f(-1) = -11
f(0) = -9
f(3) = -3
User Kelly ChowChow
by
5.7k points
1 vote

Answer:

f(-1)=-11

f(0)=-9

f(3)=-3

Explanation:

We have f(x) = 2x - 9,

  • f(-3) is the value of the function f when x=-3, then you have to replace f(x) with x=-3,


f(x) = 2x - 9\\f(-3)=2.(-3)-9\\f(-3)=-6-9\\f(-3)=-15\\eq 15

This option is incorrect.

  • f(-1) is the value of the function f when x=-1, then you have to replace f(x) with x=-1,


f(x) = 2x - 9\\f(-1)=2.(-1)-9\\f(-1)=-2-9\\f(-1)=-11

This option is correct.

  • f(0) is the value of the function f when x=0, then you have to replace f(x) with x=0,


f(x) = 2x - 9\\f(0)=2.(0)-9\\f(0)=0-9\\f(0)=-9

This option is correct.

  • f(2) is the value of the function f when x=2, then you have to replace f(x) with x=2,


f(x) = 2x - 9\\f(2)=2.(2)-9\\f(2)=4-9\\f(2)=-5\\eq5

This option is incorrect.

  • f(3) is the value of the function f when x=3, then you have to replace f(x) with x=3,


f(x) = 2x - 9\\f(3)=2.(3)-9\\f(3)=6-9\\f(3)=-3

This option is correct.

User Brunocodutra
by
6.6k points